2000
DOI: 10.1291/hypres.23.143
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Blood Pressure on the Development of Stroke, Acute Myocardial Infarction, and End-Stage Renal Disease.

Abstract: Hypertension is a known risk factor for cardiovascular disease, but few epidemiological studies have examined simultaneously the effect of baseline blood pressure on the development of stroke, acute myocardial infarction (AMI), and end-stage renal disease (ESRD). In 1983, a large, community-based mass screening covered about 14% of the adult population in Okinawa, Japan. The total number of people screened was 107,192 (51,122 men, 56,070 women). We had access to two independent registries of end-organ damage: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 35 publications
1
20
1
Order By: Relevance
“…There are substantial regional differences in the incidence and prevalence of ESRD between Japan and the United States; therefore, our results may not be applicable in other regions and countries. Mortality rates from stroke and AMI have decreased tremendously over the past 30 yr (24). Life expectancy at birth in Japan is longer than that in any other country.…”
Section: Discussionmentioning
confidence: 99%
“…There are substantial regional differences in the incidence and prevalence of ESRD between Japan and the United States; therefore, our results may not be applicable in other regions and countries. Mortality rates from stroke and AMI have decreased tremendously over the past 30 yr (24). Life expectancy at birth in Japan is longer than that in any other country.…”
Section: Discussionmentioning
confidence: 99%
“…We postulated that the lack or weakness of association between smoking and risks of stroke in most previous Japanese studies, in contrast to Caucasian studies, is due in part to the different proportions of ischemic stroke subtypes (lacunar infarction and large-artery occlusive infarction) between Japanese and Caucasians, a low statistical power to detect significant associations, and a lower concern for hypertension, a strong cardiovascular risk factor (13). We hypothesized that smoking raises the risk of total stroke, ischemic stroke, and coronary heart disease among middle-aged Japanese men, and that these trends are more evident among hypertensive men.…”
Section: Introductionmentioning
confidence: 98%
“…Levy et al [18] observed that risk for HF in hypertensive when compared to normotensive, was twice as high in men and three times higher in women [10,12]. Framingham Heart Study also reported that diabetic women, even at ages 35 to 64, were twice as likely to develop HF as diabetic men of the same age.…”
Section: Risk Factors and Aetiologymentioning
confidence: 99%